"Just a little help": A qualitative inquiry into the persistent use of uterine fundal pressure in the second stage of labor in Spain. Issue 3 (12th March 2019) - Rubashkin, Nicholas; Torres, Cinthia; Escuriet, Ramon; Dolores Ruiz‐Berdún, Maria
Abstract: Introduction: Uterine fundal pressure, or the Kristeller maneuver (KM), is a non–evidence‐based procedure used in the second stage of labor to physically force the fetus to delivery. Even though officially banned, the KM is practiced in 25% of vaginal deliveries in Spain. Methods: Using semi‐structured interviews (N = 10 women, N = 15 midwives, N = 3 obstetricians), we sought to understand how providers justify using the KM, and to describe the current circumstances in which the KM is practiced. Women described their preexisting knowledge of and experiences with the KM; providers described how they learned and practiced the KM. We used framework analysis to analyze the transcripts, and we consensus‐coded across three independent investigators. Results: Providers reported practicing a new, gentler Kristeller to which official policy did not apply. Providers knew the KM posed risks, but they assumed the risks resulted from poor technical training. Providers did not learn the KM through standard means, and they practiced it in secret. Women knew about the KM before delivery, and many had planned to refuse the procedure. Providers made women's refusal more difficult by offering the KM in coded terms as "just a little help." Women did not experience the KM as gentle, and the force of the procedure made their refusal nearly impossible. Conclusions: The normal birth policy has failed to achieve its objectives due to maternity care providers' unique logic surrounding a new KM technique. Women's ability to refuse the Kristeller is limited.